2016
DOI: 10.1080/13658816.2015.1131829
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the impact of visualization of wildfire hazard upon decision-making under uncertainty

Abstract: The paper investigates whether the methods chosen for representing uncertain geographic information aids or impairs decision-making in the context of wildfire hazard. Through a series of three human subject experiments, utilizing 180 subjects and employing increasingly di cult tasks, this research evaluates the e↵ect of five di↵erent visualizations and a text based representation on decisionmaking under uncertainty. Our quantitative experiments focus specifically on the task of decision-making under uncertaint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
72
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(99 citation statements)
references
References 60 publications
2
72
0
Order By: Relevance
“…Past research in natural hazard decision‐making has disagreed on whether changing forecast representation changes decisions. The results from this research are similar to previous research, which suggests that changing the forecast representation did not change decisions (e.g., Nadav‐Greenberg and Joslyn, ; Cheong et al ., ). These findings are contrary to Savelli and Joslyn (), who suggested that visualizations may be detrimental to decisions when compared with verbal methods of communication.…”
Section: Discussionmentioning
confidence: 97%
“…Past research in natural hazard decision‐making has disagreed on whether changing forecast representation changes decisions. The results from this research are similar to previous research, which suggests that changing the forecast representation did not change decisions (e.g., Nadav‐Greenberg and Joslyn, ; Cheong et al ., ). These findings are contrary to Savelli and Joslyn (), who suggested that visualizations may be detrimental to decisions when compared with verbal methods of communication.…”
Section: Discussionmentioning
confidence: 97%
“…Other studies have shown how design elements such as colour, symbology, data classification (e.g., stretched vs. binned), map content (including borders, landmarks etc. ), and use of gradational shading can significantly affect the way in which users interpret information on a map (e.g., Monmonier, 1996;Olson and Brewer, 1997;Severtson and Vatovec, 2012;Thompson et al, 2015Thompson et al, , 2017Cheong et al, 2016). Our personal experience has also shown this to be the case.…”
Section: Cartographic and Design Elementsmentioning
confidence: 81%
“…Well-designed visualisations can augment and enhance this cognitive processing by reducing cognitive load and facilitating inductive reasoning (Hegarty 2011;Patterson et al 2014). Accordingly, visual map products have been found to improve comprehension of hazard information when compared to non-visual communication formats such as text and tables (Severtson and Vatovec 2012;Cheong et al 2016;Cao et al 2016). However, there are many variables to consider when visually designing a map, and it can often be difficult to determine which combination of variables will support cognition and reasoning.…”
Section: Visual Designmentioning
confidence: 99%
“…Modified from Thompson et al (2015) wildfire (e.g., Cheong et al 2016), hurricane (e.g., Broad et al 2007;Sherman-Morris et al 2015), flooding (e.g., Strathie et al 2015), sea level rise (e.g., Retchless 2014), and health (e.g., Severtson and Myers 2013). For example, researchers have found that visual design of wildfire hazard maps can influence people's interest and engagement with the hazard information and also how they use it to make decisions about evacuation (Cao et al 2016;Cheong et al 2016). Similarly, visual design has been found to influence emotional and behavioural responses to tornado warning maps (Ash et al 2014).…”
Section: Exploring and Testing Different Designsmentioning
confidence: 99%